Monitoramento aéreo da regeneração natural de área florestal impactada por incêndio - Larissa Dall’Agnol; Normandes Matos da Silva; Dhonatan Diego Pessi; Camila Leonardo Mioto (Terr@ Plural)
The Cerrado experiences numerous episodes of forest fires every year, compromising the biome’s biodiversity and landscapes. The monitoring of areas degraded by fire relies heavily on remote sensing techniques, based on the digital processing of orbital and suborbital images. This study quantified plant regeneration disturbed by forest fires using high spatial resolution images obtained by drones between September 2020 and August 2021, in a 20-hectare area impacted by fire in August 2020. In the Agisoft Metashape software, RGB orthomosaics were generated for each flight, in 3 blocks of 4,800 m2 each. The pixels of the classified images express the greenness of the site, based on the Excess Green Vegetation Index, obtained in the QGIS program. After the fire and the dry season, the green vegetation covered 28.34% of the area; in January 2021, after the rainy season and natural regeneration of the vegetation, the area was covered by 81.7% green vegetation; after 4 months, the vegetation cover reoccupied 53.36% of the assessed area. A simplified QGIS operations model was developed to speed up data collection. A proposal is presented for a low-cost environmental monitoring routine, using drones and free software or software with trial versions.